Genre matters in determining success factors for online game service - Lee Dong Hyun (Global Business & Finance Review (GBFR), 2020)
Purpose: The purpose of this study is to highlight the importance of the game genres for identifying an online game's success factors. Design/methodology/approach: In this study, perceived enjoyment, ease of use and quality were suggested for probable success factors of online game service and then research model was developed to identify which factors are related with gamers' satisfaction and continuance intention. The model was tested on three major genres of online game service, role playing game (RPG), real time strategy (RTS), and first person shooter (FPS), respectively. Findings: The results showed that different online game genres were impacted differently by each element of perceived quality. The findings of this study highlight the importance of the game genres for discovering success factors of online game service. Research limitations/implications: Data used in this study may not be representative of the population of online game users because the data were gathered only in South Korea. If the future study can replicate the results with the data from other countries, it can contribute more practically to the online game market. Originality/value: This study contributes to both online game literature and genre theory by examining the relationships between success factors and satisfaction across various game genres. The empirical test results, which are meaningful not only for researchers but also for online game service providers, give evidence that each genre has different success factors.
Keywords: 650; Online game service; Genre; Success factors; Perceived quality; Satisfaction